The influence of hedonic lifestyle and self-control on consumptive purchasing behavior of NCT fans in Indonesia - Prihastutik, Nur'aini Putri; Fahmawati, Zaki Nur (Universitas Ahmad Dahlan, 2023)
The presence of K-Pop indicates that individuals tend to exhibit consumptive behavior towards themselves. This behavior arises when a fan wants to purchase items used by their idols. Unbeknownst to them, this behavior can lead to hedonic lifestyle and lack of self-control. The phenomenon of purchasing items causing consumptive behavior led to the research titled 'The Influence of Hedonic Lifestyle and Self-Control on Consumptive Purchasing Behavior of NCT (Neo Culture Technology) Fans in Indonesia.' The population in this study was 277,499 individuals found on the Twitter account @NCT_Indonesia, with a sample size of 384 people using the Accidental Sampling data collection method. The results of this study significantly show an influence on the emergence of consumptive behavior in individuals.